An Examination of Corporate Performance and Altman Z-Scores of Indian Manufacturing Firms - Liang, Foo See; Pathak, Shaakalya (Archives of Business Research, 2019)
India is a key leading economy in the Asia Pacific region. This study examines the relationship between the financial health, as measured by the Altman Z-Score, and corporate performance, as measured by the Return on Equity (ROE), of listed manufacturing companies in this market. A linear regression has been conducted between these variables to determine the magnitude and direction of their relationships. The trends of Z-Scores over a five-year period have also been analysed. The analysis covers the period from 2013 to 2017 (inclusive) and yields a statistically positive correlation between ROE and the Z-Score for the market. India registered moderate-to-strong mean and median Z-Scores. These findings further support the strong economic position of this market as an Asian giant.